PRODUKSI, PROSES DEKOMPOSISI DAN MINERALISASI SERESAH PADA HUTAN RAKYAT NGLANGGERAN KIDUL, KABUPATEN GUNUNG KIDUL, D.I.YOGYAKARTA - , Andi Gustiani Salim ([Yogyakarta] : Universitas Gadjah Mada, 2012)
People forest in Nglanggeran Kidul Sub Village, Nglanggeran Village, Patuk Sub District, Gunung Kidul District can be found in three management forms that are home garden, dry field garden, and forest. The management form is a step in management model changing depends on the treeâs crown closure. Although there were many researches about litter production and decomposition process in various places, but information of litter production, decomposition process, and change of nutrient concentration at people forest is very limited. This research was conducted in Nglanggeran Village to know tree litter production, decomposition rate, makes decomposition rate model in a sequence time, and to know concentration change of C, N, P and K elements during the decomposition process in the home garden, dry field garden, and forest. The research was done by making 20 x 20 m2 plots at home garden, dry field garden, and forest with three times of replication resulting totally nine plots. Each plot was equipped with 50 x 50 cm2 littertraps and 20 x 20 cm2 litterbags filled with 20g of air-dried litter. The result showed that the highest litter production within six months was in dry field garden (6.052 ton/ha), followed by home garden (5.637 ton/ha) and forest (4.613 ton/ha). Species dominating litter production were in-line with the highest of Important Value Index in each plot. The highest of Decomposition Index Value (T50) was found in dry field garden (0.0102) and the lowest was forest (0.0047). The highest C element content decomposed within 24 weeks was found in home garden (84.51%), followed by dry field garden (75.41%) and forest (65.92%). Nitrogen decomposition was highest happened at home garden (78.62%), dry field garden (62.37%) and forest (35.81%)